Impact of Mutations in the Coreceptor Binding Site on Human Immunodeficiency Virus Type 1 Fusion, Infection, and Entry Inhibitor Sensitivity - Reeves, Jacqueline D. (American Society for Microbiology, 2004)
An increasingly large number of antiviral agents that prevent entry of human immunodeficiency virus (HIV) into cells are in preclinical and clinical development. The envelope (Env) protein of HIV is the major viral determinant that affects sensitivity to these compounds. To understand how changes in Env can impact entry inhibitor sensitivity, we introduced six mutations into the conserved coreceptor binding site of the R5 HIV-1 strain YU-2 and measured the effect of these changes on CD4 and coreceptor binding, membrane fusion levels and rates, virus infection, and sensitivity to the fusion inhibitors enfuvirtide (T-20) and T-1249, the CCR5 inhibitor TAK-779, and an antibody to CD4. The mutations had little effect on CD4 binding but reduced CCR5 binding to various extents. In general, reductions in coreceptor binding efficiency resulted in slower fusion kinetics and increased sensitivity to TAK-779 and enfuvirtide. In addition, low CCR5 binding usually reduced overall fusion and infection levels. However, one mutation adjacent to the bridging sheet β21 strand, P438A, had little effect on fusion activity, fusion rate, infectivity, or sensitivity to enfuvirtide or T-1249 despite causing a marked reduction in CCR5 binding and a significant increase in TAK-779 sensitivity. Thus, our findings indicate that changes in the coreceptor binding site of Env can modulate its fusion activity, infectivity, and entry inhibitor sensitivity by multiple mechanisms and suggest that reductions in coreceptor binding do not always result in prolonged fusion kinetics and increased sensitivity to enfuvirtide.